Pengembangan Media Pembelajaran Flashcard berbasis Augmented Reality (AR) untuk Meningkatkan Hasil Belajar IPAS Materi Sistem Pencernaan Manusia Kelas V SDN Ngaliyan 01 - Febriany, Natasya; Bektiningsih, Kurniana (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
Students' difficulties in thoroughly understanding the human digestive system are often attributed to inadequate visualization and the use of conventional learning media that lack engagement. These factors contribute to low student learning outcomes. This study aims to develop an Augmented Reality (AR)-based flashcard learning media, and to assess its feasibility, effectiveness, and impact on improving science and social studies (IPAS) learning outcomes among fifth-grade students at SDN Ngaliyan 01. The research employed a Research and Development (R&D) method using the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. Data collection techniques included interviews, observations, multiple-choice tests, and documentation. Validation results indicated that the media received scores of 93.75% from content experts and 95% from media experts, categorized as highly feasible. Normality tests confirmed that the pretest and posttest data were normally distributed, while the T-test yielded a significance value of 0.000 (p < 0.01), indicating a significant difference in learning outcomes. The N-Gain score of 0.6831 in the small group and 0.5417 in the large group suggests medium-level effectiveness. The study concludes that the AR-based flashcard media is both feasible and effective for enhancing student learning outcomes in the topic of the digestive system. The findings imply that AR-based media can serve as an innovative alternative in IPAS instruction, fostering a more engaging, interactive, and meaningful learning experience.